CHALLENGES AND ADJUSTMENTS OF HIGH SCHOOL TEACHER-MOTHERS MANAGING YOUNG CHILDREN WHILE WORKING FROM HOME - Kimberly Rivera (LPPM UNiversitas Bina Mandiri Gorontalo, 2024)
The COVID-19 pandemic brought great changes to teaching practices, particularly for secondary school teacher-mothers balancing online instruction and childcare. This study explores the lived experiences of teacher-mothers in the Philippines during the pandemic, denoting the challenges of managing their dual roles. The central focus is on how these women coped with the tension between professional duties and motherhood, especially when both roles demand attention simultaneously. Using narrative analysis of interviews with 16 teacher-mothers of young children, the research identifies four key themes: professional and parental challenges, coping strategies, personal well-being, and the need for support. These themes reveal the complexity of their experiences, including the emotional and logistical strain of fulfilling both roles during a crisis. The study’s findings suggest that policymakers and educational institutions must prioritize the well-being of teacher-mothers by implementing supportive measures such as reasonable work arrangements and access to childcare. While limited to one Philippine province, this research offers critical insights into the unique pressures faced by teacher-mothers and notes the importance of addressing their needs for a more equitable educational system. Future research should investigate the long-term effects of the pandemic on teacher-mothers and evaluate the effectiveness of support systems introduced during this time.